Kualitas Pelayanan Akte Jual Beli di Kantor Kecamatan Kema Kabupaten Minahasa Utara - Rampengan, Royke . (JURNAL ILMIAH SOCIETY, 2015)
The provision of public services by government officials to the community (public) is the embodiment and the state apparatus functions as a public servant (servant), as well as serving the State. One of the public services provided by the district government is in the service of the deed of sale in execution of the deed of sale services to the community, there are still complaints from the public, that the performance of civil servants in the organization is quite slow, less efisein and effective and often complicate the affairs of society in particular in the service of the deed of sale and sometimes still the levies are not in accordance with provisions. The purpose of this study was to examine and explain how the Quality of Service of sale and purchase at the District Office Kema North Minahasa Regency The research methodology was qualitative research. Informants in this study was taken from the Government in the Village, Community Leaders and Communities in the District of North Minahasa Regency Kema total of 10 informants. Data were analyzed with measures of data reduction, data presentation and conclusion and verification. The results showed that the Quality of Service of sale and purchase at the District Office Kema North Minahasa Regency is quite satisfactory, wherein: the deed for the sale and purchase of service requirements imposed in accordance with the rules without any additional requirement that is intentionally added to complicate the management of the sale and purchase deed. In the management of the sale and purchase deed, if the proposed requirements are complete, it can be directly processed and can be completed in accordance with a predefined time. Purchase certificate issued by the government in the district has been able to provide legal certainty to the beneficiaries of services, because the government is very selective in assessing the validity of all documents used in the maintenance requirements of the deed of sale and purchase, if the document is invalid, the process to obtain the deed of sale and purchase directly terminated , For the cost of obtaining a deed of sale and purchase are set in accordance with the applicable legislation and the public does not charge beyond the cost already be in the process of service provision as a deed of sale all the procedures have been defined and the costs even socialized through tables placed in the waiting room when handling the sale and purchase deed so that the public already knows all the provisions in the deed of sale and purchase arrangement. In the service of the deed of sale the sub-district government did not discriminate between the position of society, because every society has an equal right to obtain services. If the management of the sale and purchase deed there are delays in obtaining, the government tells where the barriers that lead to the maintenance of the deed of sale and purchase late. Â  Key Word : Purchase Deed Service Quality